Prevailing organizational identity strength: the relationship between identity, justice perceptions and organizational citizenship behavior - Mehtap, Özge; Kökalan, Özgür; Kökalan, Özgür (Sosyal Bilimler Araştırmaları Derneği, 2014)
Studies on the organizational identity concept has gained a considerable acceleration in the recent years while, organizational identity strength has been examined as a comparatively less studied aspect of organizational identity. On the other side there are various studies which put forth the positive relation between organizational justice perceptions(OJP) and organizational citizenship behavior (OCB). The aim of this study is to reveal the effects of organizational identity strength(OIS) and OJP on the OCB. The sub-goal of the study is to present the importance of OIS on the informal organizational behaviors. In this study, survey method has been conducted with 294 white-collar workers who work in Turkish pharmaceutical industry. Data taken by the questionnaires were analyzed using SPSS 18.0 program. Hierarchical regression analysis has been implemented to put forward the independent variables’ effects on the dependent variable. Some of the hypothesis of the study has been accepted. The results also show that OIS has a considerable effect on the dimensions of OCB when compared to OJP.
Keywords: Organizational identity strength; Organizational justice perceptions; Organizational citizenship behavior